Osteoblastic cytokine response to gray and white mineral trioxide aggregate - Bidar, Maryam; Zarrabi, Mohammad Hasan; Afshari, Jalil Tavakol; Aghasizadeh, Navid; Naghavi, Neda; Forghanirad, Maryam; Attaran, Niloufar (Iranian Endodontic Journal, 2011)
INTRODUCTION: The materials used for root-end filling and perforation repair are in direct contact with live tissues e.g. bone and connective tissue; their effects however, are uncertain. The aim of this ex vivo study was to evaluate the osteoblastic secretory activity adjacent to gray and white mineral trioxide aggregate (MTA) and Intermediate Restorative Material (IRM). MATERIALS & METHODS: The studied materials were prepared and placed in 24-wells plate. Human MG-63 osteoblasts were introduced to materials after their initial set. The supernatant fluid was collected after 1, 3, and 7 days and the level of interleukin-1<span style="font-family: Symbol; color: black; font-size: 10pt; mso-bidi-language: EN-US; mso-bidi-font-family: ’Times New Roman’; mso-ascii-font-family: ’Times New Roman’; mso-hansi-font-family: ’Times New Roman’; mso-char-type: symbol; mso-symbol-font-family: Symbol;">b was measured by ELISA test. A microscopic exam was also performed to assess proliferation and viability of the cells. Kruskal-Wallis and Tukey tests were used for analysis. RESULTS: There were significant higher levels of interleukin-1<span style="font-family: Symbol; color: black; font-size: 10pt; mso-bidi-language: EN-US; mso-bidi-font-family: ’Times New Roman’; mso-ascii-font-family: ’Times New Roman’; mso-hansi-font-family: ’Times New Roman’; mso-char-type: symbol; mso-symbol-font-family: Symbol;">b in the gray and white MTA groups compared to IRM group (P<0.05). The difference in interleukin-1<span style="font-family: Symbol; color: black; font-size: 10pt; mso-bidi-language: EN-US; mso-bidi-font-family: ’Times New Roman’; mso-ascii-font-family: ’Times New Roman’; mso-hansi-font-family: ’Times New Roman’; mso-char-type: symbol; mso-symbol-font-family: Symbol;">b secretion level between two mineral trioxide aggregate groups was not significant (P>0.05). Morphologic appearance of osteoblasts adjacent to gray and white MTA was similar to normal osteoblasts in all observation periods, however cells adjacent to IRM were round, signifying cytotoxicity of the adjacent material. <span style="line-height: 115%; font-style: normal; font-family: ";Times New Roman";,";serif";; color: black; font-size: 10pt; mso-bidi-language: AR-SA; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US;">CONCLUSION:<span style="line-height: 115%; font-family: ";Times New Roman";,";serif";; color: black; font-size: 11pt; mso-bidi-language: AR-SA; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US;"> <span style="line-height: 115%; font-family: ";Times New Roman";,";serif";; color: black; font-size: 10pt; mso-bidi-language: EN-US; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US;">Human osteoblasts’ biological response to white and gray MTA is more favorable compared to IRM.